The concept of chemistry laboratory in high school - Alkan, Fatma (Eclética Química, 2024)
This research aims to determine the cognitive structures of high school students in the “chemistry laboratory” and to reveal their alternative concepts using the independent word association test and the drawing-writing technique. The sample of the study consists of 60 high school students. Content analysis was used to evaluate the data obtained from the sample group. The codes from the data were brought together and categories were created. In the analysis of the data, sentences and drawings obtained from the writing and drawing techniques were also evaluated separately. When students’ answer words are analyzed, it is seen that the concepts related to chemistry laboratory are Laboratory equipment (f:99), Chemical agent (f:41), Protective materials (f:29), Jobs (f:15), Operations in the laboratory (f:49) and Chemistry concepts (f:53). It was determined that the cognitive structures of high school students towards the concept of chemistry laboratory were related to laboratory equipment, chemical agent, protective materials, jobs, operations in the laboratory, chemistry concepts named six categories.